Second Toe Transfer and “Tandem” Free Flap for Radial Hand Injuries with Thumb Loss - Srikanth, R.; Reddy, D. Mukunda; Parvathi, R.; Rambabu, N.; K., Muralimohana Reddy; Bhanuchander, V.; Rao R, Babu (Indian Journal of Plastic Surgery, 2025)
Eleven cases of thumb loss and skin defect in the radial aspect of the hand underwent a simultaneous free flap cover and second toe transfer. Seven were emergency and four were elective. Nine of the flaps were the anterolateral thigh (ALT) flap and two were extended versions of the lateral arm flap. The mean area of tissue defect needing replacement with the free flap was 110 cm2. All the toe transfers used the second toe. The flap revascularization preceded that of the toe.The descending branch artery of the ALT flap or a branch of the radial artery, if present, was used to revascularize the transferred toe. The venous anastomosis to the flap and the toe used a combination of the superficial veins and venae comitantes of the radial pedicle. Though there were two re-explorations, only one transferred toe was lost.Among the ten patients who were evaluable at follow up, the opposition as measured by the mean Kapandji score was 6.All patients had useful grasp and thumb pinch. Secondary procedures like flap thinning and tenolysis were done in seven cases.
Keywords: second toe transfer; free flap; thumb amputation; thumb reconstruction